2022
DOI: 10.5121/ijma.2022.14103
|View full text |Cite
|
Sign up to set email alerts
|

Educational Videos for Learning Digital Illustration Concept for University Student

Abstract: To assist learning, preparation of suitable learning material is recommended along with a blended learning approach. Educational videos could be considered as a tool that can be adapted. This study aimed to develop educational videos for three (3) selected topics in Digital Illustration course offered to FirstYear Multimedia undergraduate students. ADDIE instructional design model was used to develop those educational videos. This study started with choosing a topic, designing storyboards, developing videos, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several other researchers have previously conducted similar studies on the same topic. According to the research conducted by Zain et al (2022), the user testing indicated that it was assured that the students agreed to use videos to escalate their comprehension of selected topics of the Digital Illustration course. Moreover, the results of the study were video design and usability aspects that were acceptable and reasonable.…”
Section: Introductionmentioning
confidence: 99%
“…Several other researchers have previously conducted similar studies on the same topic. According to the research conducted by Zain et al (2022), the user testing indicated that it was assured that the students agreed to use videos to escalate their comprehension of selected topics of the Digital Illustration course. Moreover, the results of the study were video design and usability aspects that were acceptable and reasonable.…”
Section: Introductionmentioning
confidence: 99%